Specifics of Transformation Projects in Universities and the Work of the Project Team - S. N. Apenko; G. Z. Efimova; M. Yu. Semenov (Высшее образование в России)
The article deals with the practices and specifics of the implementation of transformation projects in Russian universities. Particular attention is focused on the direct performers – members of project teams. The specifics of their formation are considered, the criteria necessary for employees to be included in a project team, as well as the peculiarities of such team functioning and development for more effective and productive activities are studied. The peculiarities of exclusion and withdrawal of employees from the project team – what are the reasons for it and what actions are taken by the head of the team to replace the withdrawn participant (selection of a new or redistribution of functions of the withdrawn to the remaining employees or another option) are considered separately.The conclusions presented in the article are based on the materials of an empirical sociological study conducted during the year (in the period from December 2021 to December 2022) by the method of indepth semi-formalized interviews with 78 representatives of administrative and managerial staff, scientific and pedagogical workers, heads of departments and deans of universities in three regional classical universities (in Siberian and Volga Federal Districts of the Russian Federation).Based on the results of the empirical study, the authors come to several conclusions. The transformation projects implemented in universities are associated with many diverse problems, key among which were: the destruction of agreements due to geopolitical risks; lack or complete absence of funding; varying financial success of projects; disunity of the team and lack of understanding of common goals and objectives of the project; lack of practical implementation of the project, etc.The success of the transformation project is signaled by both classical criteria called in the theory and practice of project management, for example, compliance with project deadlines, project execution within the allocated resources, and criteria less frequently mentioned in research, for example, the development of the project team, the formation of project values and norms of project culture, satisfaction of stakeholders and others. Transformation project teams are often formed spontaneously, the basis is often the potential candidate’s belonging to the required position or function, the competencies of candidates are rarely assessed, and their future competence and role statuses are planned.